The Dynamics of the Ferret Immune Response During H7N9 Influenza Virus Infection - Horman, William S. J.; Nguyen, Thi H. O.; Kedzierska, Katherine; Butler, Jeffrey; Shan, Songhua; Layton, Rachel; Bingham, John; Payne, Jean; Bean, Andrew G. D.; Layton, Daniel S. (Frontiers in Immunology, 2020)
As the recent outbreak of SARS-CoV-2 has highlighted, the threat of a pandemic event from zoonotic viruses, such as the deadly influenza A/H7N9 virus subtype, continues to be a major global health concern. H7N9 virus strains appear to exhibit greater disease severity in mammalian hosts compared to natural avian hosts, though the exact mechanisms underlying this are somewhat unclear. Knowledge of the H7N9 host-pathogen interactions have mainly been constrained to natural sporadic human infections. To elucidate the cellular immune mechanisms associated with disease severity and progression, we used a ferret model to closely resemble disease outcomes in humans following influenza virus infection. Intriguingly, we observed variable disease outcomes when ferrets were inoculated with the A/Anhui/1/2013 (H7N9) strain. We observed relatively reduced macrophage activation in lymphoid tissues which may be correlative with increased disease severity. Additionally, depletions in CD8+ T cells were not apparent in sick animals. This study provides further insight into the ways that lymphocytes maturate and traffic in response to H7N9 infection in the ferret model. As the recent outbreak of SARS-CoV-2 has highlighted, the threat of a pandemic event from zoonotic viruses, such as the deadly influenza A/H7N9 virus subtype, continues to be a major global health concern. H7N9 virus strains appear to exhibit greater disease severity in mammalian hosts compared to natural avian hosts, though the exact mechanisms underlying this are somewhat unclear. Knowledge of the H7N9 host-pathogen interactions have mainly been constrained to natural sporadic human infections. To elucidate the cellular immune mechanisms associated with disease severity and progression, we used a ferret model to closely resemble disease outcomes in humans following influenza virus infection. Intriguingly, we observed variable disease outcomes when ferrets were inoculated with the A/Anhui/1/2013 (H7N9) strain. We observed relatively reduced macrophage activation in lymphoid tissues which may be correlative with increased disease severity. Additionally, depletions in CD8+ T cells were not apparent in sick animals. This study provides further insight into the ways that lymphocytes maturate and traffic in response to H7N9 infection in the ferret model.